2009
DOI: 10.1016/j.neubiorev.2009.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Neural bases of eye and gaze processing: The core of social cognition

Abstract: Eyes and gaze are very important stimuli for human social interactions. Recent studies suggest that impairments in recognizing face identity, facial emotions or in inferring attention and intentions of others could be linked to difficulties in extracting the relevant information from the eye region including gaze direction. In this review, we address the central role of eyes and gaze in social cognition. We start with behavioral data demonstrating the importance of the eye region and the impact of gaze on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
444
2
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 521 publications
(467 citation statements)
references
References 284 publications
(424 reference statements)
17
444
2
4
Order By: Relevance
“…Furthermore, inversion did not impact the processing of human eyes while it had a detrimental effect on the processing of animal eyes (especially for dogs), reflecting a lack of expertise in accurately processing animal eyes. This particular sensitivity to human eyes is not surprising given the fundamental importance of eyes in social cognition (Emery, 2000;Itier and Batty, 2009). Furthermore, of all species, human eyes possess the largest ratio of exposed sclera size in the eye outline (Kobayashi and Kohshima, 1997).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Furthermore, inversion did not impact the processing of human eyes while it had a detrimental effect on the processing of animal eyes (especially for dogs), reflecting a lack of expertise in accurately processing animal eyes. This particular sensitivity to human eyes is not surprising given the fundamental importance of eyes in social cognition (Emery, 2000;Itier and Batty, 2009). Furthermore, of all species, human eyes possess the largest ratio of exposed sclera size in the eye outline (Kobayashi and Kohshima, 1997).…”
Section: Discussionmentioning
confidence: 93%
“…During the early stages of development, infants show a particular sensitivity for eyes to which they attend more than any other facial feature (Maurer, 1985). The eyes are central to all aspects of face processing including identity, emotion and gaze discrimination (see Itier and Batty, 2009 for a recent review) and the N170 is sensitive to eyes as shown by equally large or larger amplitudes for eyes than faces (Bentin et al, 1996;Itier et al, 2006;Itier et al, 2007;Jemel et al, 1999;Taylor et al, 2001). Because human eyes have a distinct morphology compared to eyes of other animals, including a white sclera that other species do not possess (Kobayashi and Kohshima, 1997), species sensitivity for eyes seems sensible.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such an approach fits with several eye-tracking studies that have similarly observed a particular focus on the mouth (Jones, Carr, & Klin, 2008; Klin, Jones, Schultz, Volkmar, & Cohen, 2002) and could reflect several different mechanisms. A bias toward the mouth (often also associated with a bias away from the eyes) could be associated with atypical communication in the condition (Langdell, 1978), an aversion to the socially intimidating eye region (Tanaka & Sung, 2013) or a failure to appreciate the utility of this information (Itier & Batty, 2009). Regardless of its origins, a mouth bias could negatively influence face-processing ability by preventing the exploitation of useful cues in the top half of the face (Peterson & Eckstein, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Equally, individual differences in scanning patterns could reflect atypical communicative skills in autism, driving variability in fixations to the eyes (particularly implicated in complex socio-emotional interactions) vs. the mouth (more critical for language and speech-related information) (Falck-Ytter, Fernell, Gillberg, & von Hofsten, 2010; Norbury et al, 2009). Finally, it could indicate an immature processing strategy associated with limited perceptual expertise with these social stimuli and a lack of appreciation of the importance/utility of this region (Itier & Batty, 2009). Irrespective of its origins, such an atypical profile is likely to negatively impact expertise because the eyes constitute a critical cue for face reading (Peterson & Eckstein, 2011)…”
mentioning
confidence: 99%